2023
DOI: 10.48550/arxiv.2301.06451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards strong evidence of Majorana bound state by a combined measurement of tunneling conductance and current noise

Abstract: Recently, hunting-Majorana community has reported the experimental observations of nearly quantized conductance plateau and integer Fano factor: both phenomena were believed as exclusive hallmarks of Majorana bound state. Within a unified theoretical framework, we show that zeroenergy Andreev bound states can also generate both a nearly quantized conductance plateau, and an integer Fano factor, in a sizable, continuous, yet topologically trivial parameter space. Importantly, we further propose to obtain strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In particular, in Ref. [79] it is demonstrated that in presence of MBSs a dip of the differential shot noise is always accompanied by a peak of the differential conductance. This behavior has also been observed earlier in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in Ref. [79] it is demonstrated that in presence of MBSs a dip of the differential shot noise is always accompanied by a peak of the differential conductance. This behavior has also been observed earlier in Ref.…”
Section: Introductionmentioning
confidence: 99%